Effect of the omega‐3 fatty acid plus vitamin E supplementation on subjective global assessment score, glucose metabolism, and lipid concentrations in chronic hemodialysis patients. Issue 2 (23rd November 2015) - Asemi, Zatollah; Soleimani, Alireza; Bahmani, Fereshteh; Shakeri, Hossein; Mazroii, Navid; Abedi, Fatemeh; Fallah, Melika; Mohammadi, Ali Akbar; Esmaillzadeh, Ahmad
Abstract : Scope: This study was conducted to determine the effects of omega‐3 fatty acid plus vitamin E supplementation on subjective global assessment (SGA) score and metabolic profiles in chronic hemodialysis (HD) patients. Methods and results: This randomized double‐blind placebo‐controlled clinical trial was conducted among 120 chronic HD patients. Participants were randomly divided into four groups to receive: (i) 1250 mg/day omega‐3 fatty acid containing 600 mg eicosapentaenoic acid and 300 mg docosahexaenoic acid + vitamin E placebo ( n = 30), (ii) 400 IU/day vitamin E + omega‐3 fatty acids placebo ( n = 30), (iii) 1250 mg omega‐3 fatty acids/day + 400 IU/day vitamin E ( n = 30), and (iv) omega‐3 fatty acids placebo + vitamin E placebo ( n = 30) for 12 wk. Fasting blood samples were taken at baseline and after 12‐wk intervention to measure metabolic profiles. Patients who received combined omega‐3 fatty acids and vitamin E supplements compared with vitamin E, omega‐3 fatty acids, and placebo had significantly decreased SGA score ( p < 0.001), fasting plasma glucose ( p = 0.01), serum insulin levels ( p = 0.001), homeostasis model of assessment insulin resistance ( p = 0.002), and improved quantitative insulin sensitivity check index ( p = 0.006). Conclusion: Omega‐3 fatty acids plus vitamin E supplementation for 12 wk among HD patients had beneficial effects on SGA score and metabolic profiles.